2007
DOI: 10.1093/molbev/msm049
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Past Human Male Movements in Northern/Eastern Africa and Western Eurasia: New Clues from Y-Chromosomal Haplogroups E-M78 and J-M12

Abstract: Detailed population data were obtained on the distribution of novel biallelic markers that finely dissect the human Y-chromosome haplogroup E-M78. Among 6,501 Y chromosomes sampled in 81 human populations worldwide, we found 517 E-M78 chromosomes and assigned them to 10 subhaplogroups. Eleven microsatellite loci were used to further evaluate subhaplogroup internal diversification. The geographic and quantitative analyses of haplogroup and microsatellite diversity is strongly suggestive of a northeastern Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
162
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 67 publications
14
162
1
1
Order By: Relevance
“…The controls we used in this study showed haplogroup frequencies similar to previous Y chromosome studies in Spain, [19][20][21] and most of the frequent and very frequent surnames showed haplogroup distributions similar to this control set (Table 1). For other less frequent surnames, in many cases, haplogroup composition was biased towards one or two haplogroups, indicating that sampling men with the same surname is far from random.…”
Section: Resultssupporting
confidence: 83%
“…The controls we used in this study showed haplogroup frequencies similar to previous Y chromosome studies in Spain, [19][20][21] and most of the frequent and very frequent surnames showed haplogroup distributions similar to this control set (Table 1). For other less frequent surnames, in many cases, haplogroup composition was biased towards one or two haplogroups, indicating that sampling men with the same surname is far from random.…”
Section: Resultssupporting
confidence: 83%
“…Owing to the uncertainties associated with the estimate of the evolutionary effective microsatellite mutation rates, depending on the haplogroup demographic history, 37 we considered two different population models: (1) a constant size population and (2) a single rate of m¼0.01 for exponential population growth. After calibration for the specific microsatellites used in this study, 13 we found evolutionary effective mutation rates of 7.9Â10 À4 and 1.3Â10 À3 , respectively. Estimates for R-M343/P25, R-V88, and R-V69 were obtained from 210, 98, and 26 Y chromosomes, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…However, genetic studies have been limited and mainly focused on uniparental markers and the role of the Nile basin as a corridor for human movements between northeastern and eastern Africa. [11][12][13][14] There have only been a few high-resolution analyses to date regarding the distribution of Y-specific haplogroups in the African continent. The emerging picture indicates a clear differentiation between central/western sub-Saharan and northern African populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] However, the major cultural changes in Anatolia occurred from the Bronze Age, when various civilization and empires succeeded one another over time and increasing interactions in the eastern Mediterranean resulted in the development of trading networks, military campaigns and human colonisations, particularly during the Mycenaean, the Greco-Hellenistic, Roman Republican and Imperial and later the Islamic periods. [9][10][11][12][13] From the early Middle Bronze Age onwards city-states and federations of the Hittites and the Luwians, two originally ethnically and linguistically related groups from Transcaucasia, started to infiltrate Central to Eastern and Western to Southern Anatolia, respectively. 14,15 Shortly afterward, from the 16th millennium BC, Minoan and Mycenaean colonization took place on the Anatolian west and southwest coast.…”
Section: Introductionmentioning
confidence: 99%